Measuring place attachment, identity, and memory in urban spaces: case of the Walled City of Lahore, Pakistan - Zahid, Armaghan; Misirlisoy, Damla (Journal of Architecture and Urbanism, 2021)
Public spaces are essential for any city as they define place character; they are the meeting point for social and cultural actions. Place attachment is moulded by the tie between individuals and places. The research examines the historic streets, which are remainders of their period when the pedestrian flow was predominant and had exceptional qualities that supported social action. The changed settings nowadays might have changed people’s views and the investigation was made to question and check individual’s common memory and their sensitive ties to the historic streets. The four streets from the Walled City of Lahore were selected upon their significance of history and usage. The questionnaires were prepared and the fieldwork analysis was conducted face to face and selected streets were investigated in the terms of, place attachment, identity, and memory. The outcome proved that there is a promising feeling of attachment towards the selected streets and lacking qualities of a street can be improved if look closely at the worthy streets. The study addressed an important issue of marginalization and the results from the Shah-Almi street shows that their act will create the walled city streets to lose their identity as it is formed by its users.